Excel For Accounting : Perancangan Laporan Keuangan Supplier Produk Agrikultur - Riri Rumaizha; Tiara Safitri (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This research aims to determine a model for designing simple financial reports for micro, small, and medium enterprises (MSMEs) using Microsoft Excel (EFA) at PT. FreshGo Indonesia, is a food supplier company, especially agricultural products such as fruit, vegetables, meat, seafood, and also provides superior products from Indonesian MSMEs. This research uses descriptive qualitative methods to produce financial reports consisting of profit and loss reports, and balance sheets. Data collection techniques were carried out using interviews, documentation, and observation methods. Meanwhile, the data used in this research is transaction data and other information about finances for one month. The results of this research are in the form of simple financial reports based on Microsoft Excel (EFA) which are used to record daily transactions so that financial reports can be prepared for a certain period.